What Are the Functional Roles of Piwi Proteins and piRNAs in Insects? - Dulce Santos; Min Feng; Anna Kolliopoulou; Clauvis N. T. Taning; Jingchen Sun; Luc Swevers (Insects, 2023)
Research on Piwi proteins and piRNAs in insects has focused on three experimental models: oogenesis and spermatogenesis in Drosophila melanogaster, the antiviral response in Aedes mosquitoes and the molecular analysis of primary and secondary piRNA biogenesis in Bombyx mori-derived BmN4 cells. Significant unique and complementary information has been acquired and has led to a greater appreciation of the complexity of piRNA biogenesis and Piwi protein function. Studies performed in other insect species are emerging and promise to add to the current state of the art on the roles of piRNAs and Piwi proteins. Although the primary role of the piRNA pathway is genome defense against transposons, particularly in the germline, recent findings also indicate an expansion of its functions. In this review, an extensive overview is presented of the knowledge of the piRNA pathway that so far has accumulated in insects. Following a presentation of the three major models, data from other insects were also discussed. Finally, the mechanisms for the expansion of the function of the piRNA pathway from transposon control to gene regulation were considered.